Binding Specificity of ASHH2 CW Domain Toward H3K4me1 Ligand Is Coupled to Its Structural Stability Through Its α1-Helix - Bril’kov, Maxim S.; Dobrovolska, Olena; Ødegård-Fougner, Øyvind; Turcu, Diana C.; Strømland, Øyvind; Underhaug, Jarl; Aasland, Rein; Halskau, Øyvind (Frontiers in Molecular Biosciences, 2022)
The CW domain binds to histone tail modifications found in different protein families involved in epigenetic regulation and chromatin remodeling. CW domains recognize the methylation state of the fourth lysine on histone 3 and could, therefore, be viewed as a reader of epigenetic information. The specificity toward different methylation states such as me1, me2, or me3 depends on the particular CW subtype. For example, the CW domain of ASHH2 methyltransferase binds preferentially to H3K4me1, and MORC3 binds to both H3K4me2 and me3 modifications, while ZCWPW1 is more specific to H3K4me3. The structural basis for these preferential bindings is not well understood, and recent research suggests that a more complete picture will emerge if dynamical and energetic assessments are included in the analysis of interactions. This study uses fold assessment by NMR in combination with mutagenesis, ITC affinity measurements, and thermal denaturation studies to investigate possible couplings between ASHH2 CW selectivity toward H3K4me1 and the stabilization of the domain and loops implicated in binding. The key elements of the binding site—the two tryptophans and the α1-helix form and maintain the binding pocket— were perturbed by mutagenesis and investigated. Results show that the α1-helix maintains the overall stability of the fold via the I915 and L919 residues and that the correct binding consolidates the loops designated as η1 and η3, as well as the C-terminal. This consolidation is incomplete for H3K4me3 binding to CW, which experiences a decrease in overall thermal stability on binding. Loop mutations not directly involved in the binding site, nonetheless, affect the equilibrium positions of the key residues.